Synthesis of Neutral SiO𝟐/TiO𝟐 Hydrosol and Its Application as Antireflective Self-Cleaning Thin Film - Chiahung Huang; Hsunling Bai; Yaoling Huang; Shuling Liu; Shaoi Yen; Yaohsuan Tseng (International Journal of Photoenergy)
A neutral SiO2/TiO2 composite hydrosol was prepared by a coprecipitation-peptization method using titanium tetrachloride and silicon dioxide hydrosol as precursors. It is not only an antireflective self-cleaning coating material but also an environmental-benign material. Even heated at 700°C for 5 minutes in the tempering process, the as-prepared SiO2/TiO2 thin film still demonstrated antireflection and photocatalytic self-cleaning effect. The SiO2/TiO2 thin film increased near 2% of transmittance; however, the TiO2 thin film decreased 5% of transmittance at least. In addition to antireflection, the SiO2/TiO2 thin film decomposed the surface coated oleic acid under ultraviolet light and showed superhydrophilicity under dark for two days. The SiO2/TiO2 thin film also showed good photocatalytic degradation of methylene blue. With these antireflection, persistent superhydrophilicity, and photocatalytic self-cleaning effects, this prepared neutral SiO2/TiO2 hydrosol would be a good coating material for tempered glass and other building materials.